Izin Pengelolaan Pertambangan Batu Bara Berdasarkan Undang-Undang tentang Pertambangan Mineral dan Batubara di Indonesia - Faturachman Shidiq (Program Studi Ilmu Hukum, Universitas Kuningan, 2025)
This article aims to identify and analyze coal mining management permits based on Indonesian laws and regulations. The research method used in this paper is a normative juridical research method. The results show that coal management permits in Indonesia are regulated by Law Number 3 of 2020, which amends Law Number 4 of 2009 concerning Mineral and Coal Mining. This law emphasizes sustainable natural resource management, community involvement, and optimizing added value through domestic processing and refining activities. The conclusion is that the implementation of mining regulations faces several challenges, such as conflicts between economic, social, and environmental interests, as well as addressing illegal mining activities. Legal protection for communities living around mining areas must be based on Pancasila values ​​and prioritize the principle of social justice. To maximize the benefits of the mining sector, a regulated, transparent, and sustainability-oriented licensing system is required.